READING AS A STRATEGY FOR DISSEMINATING SCIENTIFIC IDEAS IN BASIC EDUCATION - Ricardo Nunes da Silva, Anderson (Revista Gênero e Interdisciplinaridade, 2026)
The article reflects on the indispensability of science communication with the aim of highlighting the relevance of using popular science texts in an educational context. The study highlights that disseminating scientific texts makes scientific knowledge accessible to everyone, playing a crucial role in the development of critical thinking and the ability to make decisions. It advocates for the adoption of pedagogical practices that contribute to scientific literacy and the use of popular science texts as tools for fostering more critical, engaged citizens capable of facing the challenges of contemporary society. It is concluded that the lack of scientific and technological literacy affects individuals’ social lives, particularly in distinguishing between true and false information, and consequently, in the spread of unfounded news and information. Science is a language, being scientifically literate means knowing how to decipher the language of nature and the world, striving for its constant evolution.